KERESAHAN SOSIAL PADA MASYARAKAT SEKITAR DAERAH PERTAMBANGAN TANPA IZIN (PETI) - Syaifudin Suhri Kasim; Rosnah (Halu Oleo University, 2023)
The aim of this research is to explain the social unrest caused by the negative impacts of unlicensed mining activities (PETI). This research is descriptive qualitative in nature. Descriptive studies are used for two reasons. First, this type of research is carried out to provide an overview of the social or psychological characteristics of a particular group or community. Second, because there are groups and communities that show differences in their behavior. Data was collected through interviews, observation and documentation, and analysis was carried out descriptively qualitatively. Research shows that village communities experience social problems as a result of unlicensed mining activities (PETI). This is in accordance with research findings which show that the majority of people (72%) are worried about the existence of gold mining companies because of air pollution produced by road dust produced by mining activities.